Microwave-assisted polymer synthesis of polycondensation materials for high performance coatings - Vidales Herrera, Jessica Vidales (2023)
Polymers have become important industrial materials due to their versatility and wide range of properties and applications. In 2020 worldwide plastics production reached 367 million tons. One of the challenges that this sector faces is the long reactor cycle times associated with the current manufacturing technology, which acts as a bottleneck and limits production volumes. Efforts towards process intensification based on the development of innovative systems and techniques capable to deliver faster production rates with less energy and waste are of great interest for manufactures as even small reductions in cycle time could result in significant economic and environmental benefits.